An Oxidative Stress-Related Gene Pair (CCNB1/PKD1), Competitive Endogenous RNAs, and Immune-Infiltration Patterns Potentially Regulate Intervertebral Disc Degeneration Development - Cao, Shuai; Liu, Hao; Fan, Jiaxin; Yang, Kai; Yang, Baohui; Wang, Jie; Li, Jie; Meng, Liesu; Li, Haopeng (Frontiers in Immunology, 2021)
Oxidative stress (OS) irreversibly affects intervertebral disc degeneration (IDD) pathogenesis. Certain non-coding RNAs act as competitive endogenous RNAs (ceRNAs) that regulate IDD progression. Analyzing the signatures of OS-related gene (OSRG) pairs and regulatory ceRNA mechanisms and immune-infiltration patterns associated with IDD may facilitate IDD distinguishment and reveal the underlying mechanisms. Therefore, OSRGs were downloaded and identified using the Gene Expression Omnibus database. Functional-enrichment analysis revealed OS-related pathways and processes. A ceRNA network was generated. Differentially expressed OS-related genes (De-OSRGs) were used to construct differentially expressed OS-related gene pairs (De-OSRGPs). The De-OSRGPs were screened, and candidate De-OSRGPs were identified. Immune cell-related gene pairs were selected via immune-infiltration analysis. A potential long non-coding RNA (lncRNA)–microRNA (miRNA)–messenger RNA (mRNA) axis was uncovered, and clinical values were assessed. Eighteen De-OSRGs were identified that were primarily related to intricate signal-transduction pathways, apoptosis-related biological processes, and multiple kinase-related molecular functions. A ceRNA network consisting of 653 lncRNA–miRNA links and 42 mRNA–miRNA links was constructed. Three candidate De-OSRGPs were screened out from 13 De-OSRGPs. The abundances of resting memory CD4+ T cells, resting dendritic cells, and CD8+ T cells differed between the control and IDD groups. CD8+ T cell infiltration correlated negatively with cyclin B1 (CCNB1) expression and positively with protein kinase D1 (PKD1) expression. CCNB1–PKD1 was the only pair that was differentially expressed in IDD, correlated with CD8+ T cells, and displayed better predictive accuracy than individual genes. The PKD1–miR-206-5p–AP000797 and CCNB1–miR-212-3p–AC079834 axes potentially regulated IDD. Our findings indicate that the OSRGP, CCNB1–PKD1, which regulates oxidative stress during IDD development, provides a robust signature for identifying IDD. The OSRGP and increased infiltration of CD8+ T cells (which play important roles in IDD) were functionally associated. Thus, the OSRGP CCNB1–PKD1 may be a promising IDD target.